Effect of fortification of commercial glycerol and crude glycerol to straw based mixed substrate on fermentation kinetics and energy value - Savitha, G; Lokesha, E; Suson, Thingujam; Sondur, S N; Srinivas, Bandla (Indian Journal of Dairy Science, 2019)
The study evaluated the effect of commercial grade pure glycerol (PG) and, crude glycerol (CG) which was obtained during biodiesel production on rumen fermentation kinetics in vitro. Glycerol purity of both the sources was 99.9% and confirmed with GC-MS. CG was little alkaline with 7.11 pH and consisted total tannins, alkaloids and flavonoids 24.09±3.21, 16.63±3.97 and 20.52±4.11µg/ml, respectively than PG. In vitro fermentation kinetics (IVFK) and substrate utilization by rumen microbes was studied by applying first order kinetics to in vitro gas production (IVGP) technique. Substrate having roughage to concentrate ratio of 60:40 was used without glycerol fortification (control) or fortified with10% PG or CG. Total gas production (TGP) was significantly (P